(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article under discussion reveals using information technologies to foster communicative competence of students in teaching foreign languages. The author of the article considers that use of the information technologies in the formation of speaking skills is appropriate at different stages of training, as digital educational content helps to diversify the same tasks, increases the motivational component of students, contributes to a better mastering of the material, increases the quality of knowledge, provide students with live communication with native speaker